Characteristics of vertical velocities estimated from drop size and fall velocity spectra of a Parsivel disdrometer - D.-K. Kim; C.-K. Song (Atmospheric Measurement Techniques, 2018)
Vertical air velocities were estimated from drop size and fall velocity spectra observed by Parsivel disdrometers during intensive field observations from 13 June to 3 August 2016 around Mt. Jiri (1915 m a.s.l.) in the southern Korean Peninsula. Rainfall and wind velocity data measured by Parsivel disdrometers and ultrasonic anemometers, respectively, were analyzed for an orographic rainfall event associated with a stationary front over Mt. Jiri on 1 July 2016. In this study, a new technique was developed to estimate vertical air velocities from drop size and fall velocity spectra measured by the Parsivel disdrometers and investigate characteristics of up-/downdrafts and related microphysics on the windward and leeward sides of the mountain. To validate results from this technique, vertical air velocities between the Parsivel disdrometers and anemometers were compared at different locations and were shown in quite good agreement with each other. It was shown that upward motion was relatively more dominant on the windward side and even during periods of heavy rainfall. In contrast, downward motion was more dominant on the leeward side during nearly the same periods of heavy rainfall. Occurrences of upward and downward motion were digitized as percentage values as they are divided by a total count of occurrences during the entire period. On the windward (leeward) side, the percentages of upward (downward) motion were much larger than those of downward (upward) motion. The mean rainfall intensity on the leeward side was stronger than on the windward side, suggesting that most of the rainfall on the leeward side was relatively more affected by the downward motion. With the estimated vertical air velocities, histogram characteristics of rainfall parameters were also examined between the windward and leeward sides.